Analisis Celah Hukum Terkait Pengaturan Sanksi Administratif Pada Penyelenggaraan Rumah Susun - Hendryk, Yofan (Magister Kenotariatan Universitas Surabaya, 2024)
Indonesia is a large country consisting of tens of thousands of islands with a total of more than 270 million people scattered in it. As a state of law with a welfare state concept that recognizes the protection and recognition of human rights. About this, a horizontal residential development was organized which is now named as a condominium. Condominiums are organized to meet the needs of decent housing for the people of Indonesia, especially low-income people. This is organized to meet the need for housing which is relatively increasing from year to year while the amount of land space in this case land is limited so that it will decrease over time. In condominium management, positive law in Indonesia regulates P3SRS which is a legal entity consisting of residents or condominium owners and has the duty and obligation to manage all common interests and ownership in the condominium. Positive law in Indonesia regulates the obligation of the residents to form the residents association and the obligation of the builder to facilitate the formation of the P3SRS. This research focuses on reviewing and analyzing related legal provisions in providing administrative sanctions against the occupants and builders when the residents assiociation is not formed. The results of this study indicate that there is a legal gap and legal uncertainty related to the provision of administrative sanctions, which only regulates the provision of administrative sanctions against residents who do not form resdents association, while the builders are not regulated by the same administrative sanctions. Thus resulting in the absence of legal certainty in these provisions and leading to various legal problems. The research method used in this research is normative juridical, namely research that analyzes through principles, theories, and legal norms. The approach used is the statute approach through the provisions of the law or positive law and case approach, namely through relevant legal cases to answer the subject matter of this research.